Evaluasi Kelengkapan Dan Kualitas APD Bagi Pekerja Sumur Migas - Arga Aridianta, Dadang; Callista Elvania, Nindy; Cahya Anggara, Oktavianus (Universitas Islam Lamongan, 2025)
Oil and gas business activities include a series of activities related to the exploration, production, processing, and distribution of oil and gas. The oil and gas industry is one of the high-risk and dangerous sectors. Therefore, occupational safety management is very important for companies to prevent accidents in the workplace. The purpose of this study is to find out the application of the use of workers' personal protective equipment required by the company and to find out the company's efforts in increasing the mandatory application of personal protective equipment. This research was conducted at PT. X in the field of oil and gas exploration and production. The data collection method was carried out by interviews and document studies. The sampling technique of this study was carried out with certain considerations or purposive sampling. The sample consisted of 24 individuals, including 3 field supervisors with the position of driller, and 21 field workers with the positions of derrickman, floorman, and mechanic. The analysis method used is Importance-Performance Analysis (IPA). The results of the analysis are shown by the Importance-Performance Analysis (IPA) diagram which has 4 quadrants. The variables of comfort and effectiveness are included in quadrant A (top priority), while the variables of flexibility, durability, satisfaction, and awareness are included in quadrant B (maintain), the prudent and clean variables are included in quadrant C (low priority), and there are no variables categorized as quadrant D (ignore). The company's efforts as part of increasing the mandatory implementation of personal protective equipment are through the implementation of safety introductions, safety briefings, as well as by installing posters and safety signs in the work environment